Invisible chains : themes of gender and violence in Malaysian literature in English - Michelle Shalini Ramakrishnan,; Ruzy Suliza Hashim,; Noraini Md Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2019)
The paper will focus on the treatment of domestic violence in literary works of Malaysian Literature in English (MLE) writers. The paper will primarily analyse intimate partner violence and examine these violence, as portrayed in the selected texts. MLE provides insights into the thematic concerns of Malaysian writers, giving rise to pertinent issues that affect a country’s well-being and its people. Several scholars have studied some of the selected works, and their works centre on the thematic concerns such as nationhood and nation-building, but issues of domestic violence have been dismissed as unimportant. Departing from previous research, this paper examines the novelistic representations of domestic violence with the aim to create awareness and giving them visibility.